1996
DOI: 10.1046/j.1365-2036.1996.89261000.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomized trial of low‐dose versus high‐dose topical anaesthesia in unsedated upper gastrointestinal endoscopy

Abstract: High-dose pharyngeal anaesthesia reduces patient discomfort during unsedated upper gastrointestinal endoscopy. However, patient tolerance is also influenced by clinical features, which might be useful in deciding which patients are suitable for this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 0 publications
3
21
0
1
Order By: Relevance
“…Jameson et al [9] found that lignocaine spray of 100 mg is superior to 50 mg with regard to reduction in patient discomfort and fewer gags in sedated EGD. Mulcahy et al [10] reached a similar conclusion when comparing 30-and 100-mg lidocaine spray in unsedated EGD. However, no direct comparison between 20-and 60-mg lignocaine as a topical anesthesia was performed in the past.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Jameson et al [9] found that lignocaine spray of 100 mg is superior to 50 mg with regard to reduction in patient discomfort and fewer gags in sedated EGD. Mulcahy et al [10] reached a similar conclusion when comparing 30-and 100-mg lidocaine spray in unsedated EGD. However, no direct comparison between 20-and 60-mg lignocaine as a topical anesthesia was performed in the past.…”
Section: Discussionsupporting
confidence: 52%
“…Mulcahy et al [10] found that more than onethird of patients request sedation after undergoing unsedated EGD. The use of midazolam as sedation in EGD is found to be beneficial and to improve patient tolerance [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…Both studies used drugs other than lidocaine, where oxybuprocaine is more potent and benzocaine is less potent than lidocaine 8. Furthermore, the patients in both studies also received sedation, which likely biases the assessment of the effects of topical anesthesia as sedation induces antegrade amnesia 9. A recent study by Canon et al5 compared the effectiveness of a lidocaine spray with a lozenge in a randomized placebo-controlled study in 191 unsedated consecutive patients 5.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, high (100 mg) and low doses (30 mg) of the lidocaine spray were compared. A decrease was detected in the discomfort of patients who were administered high doses (22). In addition, we believe that the gel's lubricating effect is also important for this satisfaction.…”
mentioning
confidence: 79%